Canadian-American relations: Ready for a thaw. (Economist, 2006)
Canada's new government is hoping to mend relations with the U.S. In recent years, Canada's access to the highest levels of U.S. government has been steadily eroded, as it has chosen not to join America's war in Iraq or to participate in its plans for missile defense. Stephen Harper, Canada's newly elected Conservative prime minister, is now seeking to rebuild the relationship, and he has made a start by promising to increase defense spending and to strengthen border and port security.